Penatalaksanaan Fisioterapi Pada Kasus Bell's Palsy Di RSUP Dr. Sardjito Yogyakarta - Dwi Puspaningtyas, Ratih; , Sugiono S.Fis, MH.Kes (2015)
Background: Bell's Palsy is a weakness of facial muscle with the type of lower motor neurons causes by idiopathic facial nerve involvement outside the central nervous system, in the absence of other neurologic disease. Which can lead to a problem of physical capasity in the form of Infra Red (IR), Faradic (electrical Stimulation), Massage, and Exercise Mirror which can increase the strength of muscle of the face and can restore functional ability of facial muscles on the condititon of Bell's Palsy. Objective: Benefits ans purpose in granting Infra Red (IR), Faradic (electrical Stimulation), Massage, and Exercise Mirror can improve strength facial muscles and restore functional ability of facial muscles on the condition of Bell's Palsy. Result: After the therapy 6 times in getting the result increas examination of the facial muscles to scale Ugo Fisch rest position (T1= 14 - T6=14), Frowning (T1= 3 - T6= 7), Blinfolding (T1= 9 - T6= 21), Smiling (T1= 9 - T6= 21), Whistling (T1= 3 - T6= 3) and the functional ability (T1= 38 - T6= 66). Conclusion: Ny. SS with the case of Bell's Palsy, After treatment for 6 times with modalities Infrared (IR), Faradic (Electrical Stimulation), massage, and exercise Mirror an increase in facial muscle strength and functional abilities Increase in facial muscles.